Quality of life in university teachers: a systematic review. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2018)
INTRODUCTION: Concern about the issue of Quality in University Teaching has been more visible in governmental and social entities than within the teaching community itself. For this reason we have started this research process with the aim of finding methodologies identified in the measurement of Quality of Life in University Teachers through an extensive literature review through a systematic review. METHODS: This research corresponds to a qualitative study, cross-sectional and descriptive, which aims to establish is the best method of measuring quality of life in University Teachers using PICO methodology. RESULTS: These studies reveal different methodologies for measuring quality of life, among which we find: Open interviews, semi-structured interviews, group discussion, web questionnaires, adaptation to the Adult Quality of Life Scale (EVCA), GENCAT Scale. ANALYSIS AND DISCUSSION: It is evident that the best method of measuring the Quality of Life in University Teachers are the standardized scales, since, due to their design, they present greater ease of qualification; These are produced in only one format, so they are faster, the results are more reliable due to statistical analysis. CONCLUSIONS: The concept of Quality of Life in relation to university teaching can be seen from different perspectives, among which is quality in the replication of education, in a process of transformation and in the way of life
Keywords: faculty; interviews; reliability; scales; quality of life.